Strengthening Religious Awareness Through the Implementation of Ahlussunnah wal Jama'ah Values in Sekeangkrih Village, Bandung Regency - Ahmad Khori; Timbul Silalahi; Zeevano Albariq Baskara; Katarina Sinulingga; Rifki Solehudin Kahfi; Danu Supriatna (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Awareness of worship is a crucial element in the lives of Muslims, but in Kampung Sekeangkrih, Cileunyi Wetan Village, Bandung Regency, there is still a low level of awareness of worship and participation in regular religious lectures. The lack of understanding of the values of Ahlussunnah wal Jama'ah (ASWAJA) and the influence of technological developments and digital media that encourage individualistic attitudes are the main challenges. This study fills the research gap on how the application of ASWAJA values can increase religious awareness in rural communities. This study aims to analyze the role of the implementation of Ahlussunnah wal Jama’ah (ASWAJA) values in strengthening community worship awareness through a contextual socio-religious approach that is responsive to digital dynamics. Qualitative methods were used to collect data through observation and in-depth interviews with 15 informants, including religious leaders, community leaders, and residents who are active and less active in worship. Qualitative descriptive analysis was conducted to understand the level of understanding and factors influencing the community's worship practices. The results revealed that religious awareness remains low due to limited religious understanding, the influence of digital media, and the lack of role models among religious leaders. The application of the values of moderation, togetherness, and social responsibility contained in ASWAJA has the potential to strengthen collective religious awareness. This study recommends innovative and contextual religious guidance strategies to build a culture of mutual reminders in worship, while utilizing digital media positively. These findings are important as a basis for developing religious programs that are responsive to social and technological dynamics in rural communities.